Influential Factors in Exclusive Breastfeeding: The Role of Advertising Campaigns and Positive Close Relatives - Rostinah; Anggriani, Dini; Muttaqin, Mundir; Supriadin (The Indonesian Institute of Science and Technology Research, 2024)
This study aimed to investigate the impact of Advertising Campaigns and Positive Close Relatives on exclusive breastfeeding practices among mothers in the postpartum period. A cross-sectional study was conducted among 66 mothers with infants aged 6-11 months in the Rasanae Timur Primary Health Care area in Kota Bima, NTB. Data were collected through structured interviews. Bivariate and multivariate analyses were employed to assess the associations between independent variables (Advertising Campaign, Positive Close Relatives) and the dependent variable (exclusive breastfeeding). The study found significant associations between exclusive breastfeeding and Advertising Campaigns, as well as Positive Close Relatives. Mothers exposed to Advertising Campaigns were more likely to opt for formula feeding over exclusive breastfeeding. Conversely, positive Positive Close Relatives, including encouragement and practical assistance, correlated with higher rates of exclusive breastfeeding. However, Maternal Occupation did not demonstrate a significant impact on exclusive breastfeeding practices. These findings underscore the critical role of both external influences, such as Advertising Campaign, and internal familial support in shaping maternal infant feeding decisions.